2019
DOI: 10.1186/s12920-018-0437-8
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the 3D chromatin organization coordinating with gene expression regulation in B-cell lymphoma

Abstract: Background: Eukaryotes compact chromosomes densely and non-randomly, forming three-dimensional structures. Alterations of the chromatin structures are often associated with diseases. In particular, aggressive cancer development from the disruption of the humoral immune system presents abnormal gene regulation which is accompanied by chromatin reorganizations. How the chromatin structures orchestrate the gene expression regulation is still poorly understood. Herein, we focus on chromatin dynamics in normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Previous studies [ 36 , 37 ] have shown an enrichment of B-to-A compartment reorganization from one cell type to another in regions with upregulated genes. Therefore, we asked if the B-to-A transitions were enriched in regions containing upregulated marker genes associated with the cell types in our datasets.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies [ 36 , 37 ] have shown an enrichment of B-to-A compartment reorganization from one cell type to another in regions with upregulated genes. Therefore, we asked if the B-to-A transitions were enriched in regions containing upregulated marker genes associated with the cell types in our datasets.…”
Section: Resultsmentioning
confidence: 98%
“…Because mutagenesis and chromatin conformation are dynamic processes, future systematic analyses over time may be desirable to refine the results of this study. Nevertheless, the folding patterns of chromatin compartment domains are highly conserved within B-cells, and even during malignant B-cell transformation, gene switching from the active to the inactive compartment was only 3.1% [ 55 ]. Whether specific chromatin organizations affecting CLL and FL may alter our findings, remains unanswered and will require technically challenging Hi-C experiments on human primary lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Later, two studies [34,222] reported that upon activation of the ER-alpha, transcriptional changes entail coordinated responses at the chromatin structure level. Finally, Hi-C experiments of genome-wide chromatin interactions have identified a switch from B to A compartments accompanied by up-regulation of their resident genes in breast cancer [223] and B-cell lymphoma [224].…”
Section: Omic Developments To Study Cancer Genomicsmentioning
confidence: 99%